Effects of cultural backgrounds on interpersonal interactions among students from different culture and nationalities: an empirical study on Stamford College business students - Gowindasamy, Maniyarasi (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study was conducted to investigate the effects of different cultural background on the Interpersonal Communication (IPC) among local and international students in Stamford College, a private college in Selangor, Malaysia. A mixed method was used to conduct this study. The main method was quantitative then a simple interview was conducted to enrich the data and to provide more detail. The study was participated by 250 business students from three different levels of study. The quantitative study had 140 local and 110 international students of business programme, and only 14 of the students were interviewed for the qualitative study. These 14 students were chosen based on random sampling of their nationality. The result of the study shown a positive result, the huge majority of participants reported that their different cultural backgrounds had a positive impacts on their interactions among different background and nationalities students. The results are supportive of the positive effects of cultural and student daily interactions. Findings of this study may encourage both local and international students from different cultural to experience new multicultural environment and improve their interpersonal interaction with people from different backgrounds.